Application of Discovery Learning Model Towards Improving Geography Learning Outcomes of Grade IPS-X at State Senior High School 1 Parigi, Parigi District Gowa Regency - H, Hasriyanti; Mannan, Abdul; Alifah, Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Classroom action research that aims to determine for improve learning outcome on study Geography in SMA Negeri 1 Parigi. Sum of subject on research were 20 students. The reason choice location research, 1) teachers Geography worried about learning outcome. 2) Location research near by location disaster (Bawakaraeng collapse). This research does during 2 cycles, with each cycle consisting of planning, action, observation/evaluation and reflection. Each cycle consisting of each meeting. The data was collected used by sheet of test and sheet for observation activity/ student activities. (1) Student can answer question from teacher/ other student increase up to 5%. (2) Student ask when study increase up to 10%. (3) Students active on discussion increase up to 20% (4) The student do activity out learning (play game, disturb his friend etc) less until 20%. Before do this research discovery learning their value average pretest was 52,5. But, after application discovery learning theirs value average increase become 70,5 on cycle I and Value 82 on cycle II. Happen increase value average student up to 18,00 from pretest to cycle I and 11,5 from cycle I to cycle II. Conclusion from this research is application discovery learning can increase learning outcome.